2020
DOI: 10.1097/md.0000000000020081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of XiangShaLiuJunZi decoction combined with S-1 as maintenance therapy for stage III or IV gastric carcinoma and colorectal carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In fact, “preventive treatment” is one of the core concepts of traditional Chinese medicine. In clinical practice, many traditional prescriptions have been applied, such as the Sijunzi decoction ( Zhong et al, 1997 ; Cai et al, 2008 ), Xiangshaliujunzi decoction ( Lv et al, 2017 ; Hong et al, 2020 ), etc. Among these decoctions, Codonopsis pilosula (Franch.)…”
Section: Introductionmentioning
confidence: 99%
“…In fact, “preventive treatment” is one of the core concepts of traditional Chinese medicine. In clinical practice, many traditional prescriptions have been applied, such as the Sijunzi decoction ( Zhong et al, 1997 ; Cai et al, 2008 ), Xiangshaliujunzi decoction ( Lv et al, 2017 ; Hong et al, 2020 ), etc. Among these decoctions, Codonopsis pilosula (Franch.)…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that traditional Chinese medicine (TCM) combined with chemotherapy can improve CRC treatment, through reducing postoperative ileus and urinary, improving the tolerance of patients and the complications and resistance of chemotherapy, remodeling the gut microbiota and the tumor microenvironment, suppressing thymidylate synthase, and preventing cancer recurrence and metastasis, etc. ( Tan et al, 2008 ; Ye et al, 2015 ; Liu et al, 2017a ; Sui et al, 2017 ; Liu et al, 2018a ; Zhang et al, 2018 ; Lv et al, 2019 ; Hong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Modern research shows that XSLJZ can be used to treat nausea, vomiting, abdominal distension, diarrhea, and diarrhea. [ 17 , 18 ] Therefore, it is often used to treat CINV in China. The clinical effect of XSLJZ on CINV may be achieved by up-regulating the production of ghrelin, cholecystokinin and vasoactive intestinal polypeptides and increasing the levels of these neuropeptides in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang-Sha-Liu-Jun-Zi (XSLJZ) created by Yunbo Ke, a doctor of Chinese medicine in the Qing Dynasty, is a classic formula of TCM [16] . Modern research shows that XSLJZ can be used to treat nausea, vomiting, abdominal distension, diarrhea, and diarrhea [17,18] . Therefore, it is often used to treat CINV in China.…”
Section: Introductionmentioning
confidence: 99%